2000
DOI: 10.1021/jp000947n
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Can Open the Photoisomerization Pathway for the Direct Photodissociation Reaction of Diiodomethane:  Transient Resonance Raman Observation of the Isodiiodomethane Photoproduct from Ultraviolet Excitation of Diiodomethane in the Solution Phase

Abstract: We report transient resonance Raman experiments that identify isodiiodomethane as the photoproduct responsible for the ∼385 nm absorption band observed following ultraviolet excitation of diiodomethane in liquid solutions. Comparison with previously reported gas-phase experiments and solution-phase resonance Raman and femtosecond transient absorption results suggest that solvation leads to appreciable production of the isodiiodomethane (H2C−I−I) photoproduct via the interaction of the initially formed CH2I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(145 citation statements)
references
References 42 publications
16
129
0
Order By: Relevance
“…17,41 Our calculations (vide infra) also predict a very strong absorption band for iso-CH 2 Br-I. Picosecond time-resolved Raman measurements on CH 2 BrI 39 along with studies of related dihalomethane compounds 3,4,9,27,29,32,[66][67][68][69][70] confirm the assignment to iso-CH 2 Br-I.…”
Section: A Assignment Of Iso-ch 2 Br-imentioning
confidence: 55%
See 1 more Smart Citation
“…17,41 Our calculations (vide infra) also predict a very strong absorption band for iso-CH 2 Br-I. Picosecond time-resolved Raman measurements on CH 2 BrI 39 along with studies of related dihalomethane compounds 3,4,9,27,29,32,[66][67][68][69][70] confirm the assignment to iso-CH 2 Br-I.…”
Section: A Assignment Of Iso-ch 2 Br-imentioning
confidence: 55%
“…We also note that Phillips and coworkers rule out contributions from CH 2 I in their transient Raman experiments performed in cyclohexane. 41,53,70 Thus, the absence of the ∼280 nm band in the transient spectrum makes assignment of the 360 nm absorption band in cyclohexane to CH 2 I unlikely.…”
Section: (3) Time-resolved Resonance Raman Measurements Observementioning
confidence: 99%
“…[129] Nanosecond [130] and picosecond [131] transient resonance Raman investigations demonstrated that isodiiodomethane 83 is mostly responsible for the intense absorption band at about 385 nm. Both 83 and the CH 2 I 2 ϩ cation appear to contribute to the weak transient absorption band at approximately 570 nm.…”
Section: Interactions Of Carbenes With Halogensmentioning
confidence: 99%
“…[1][2][3] Diiodomethane (CH 2 I 2 ) has received much attention because of its intriguing condensed-phase UV photochemistry, namely the formation of a metastable iso-CH 2 I-I isomer product in a high quantum yield, as revealed by isolation in Ar and N 2 matrices [4,5] and femtosecond pumpprobe (fs-PP) spectroscopy of CH 2 I 2 in solution. [6,7] The nature of the isomer product species has been confirmed by nanosecond resonance Raman (ns-RR) spectroscopy, [8] picosecond time-resolved resonance Raman (ps-TR 3 ) spectroscopy, [9] and 100 ps time-resolved X-ray diffraction (tr-XD) [10] studies. Vibrationally hot iso-CH 2 I-I occurs within several picoseconds, and is attributed to recombination of nascent CH 2 IC and IC fragments following photodissociation of one of the two CÀI bonds in CH 2 I 2 .…”
Section: Introductionmentioning
confidence: 95%